The science of emotion : research and tradition in the psychology of emotions - Cornelius, Randolph R., 1953- (Upper Saddle River, N.J. : Prentice Hall, 1996)
The author of this essential text on the science of emotion examines each of the four major theoretical points of view representing most contemporary research on the subject: Darwinian, Jamesian, Cognitive, and Social Constructivist. He describes the major premises of each tradition, compares them to one another, briefly details the major research defining each point of view, and concludes each chapter with recommendations for further reading. Randolph R. Cornelius emphasizes the importance of the scientific and objective approach to the study of emotions and stresses the value of examining each perspective in its own terms as well as those of the other three. He includes many examples from contemporary life and literature to help students identify with the topics covered. An entire chapter is devoted to contrasting how each of the four traditions would explain four different emotions: fear, anger, love, and hope. The text closes with an appendix providing an overview of the neurophysiology of emotion.
Emotions in science and everyday life -- Snarling dogs, cowering cats, and weeping humans: the Darwinian perspective -- Listening to the cries and whispers of the articulate body: the Jamesian perspective -- Feeling is thinking: the cognitive perspective -- Emotions and the politics of everyday life: the social constructivist perspective -- Of elephants and blind men: comparing the Darwinian, Jamesian, cognitive, and social constructivist perspectives on emotion -- Concluding unscientific postscript: emotions and you.
Includes bibliographical references (pages 232-251) and index.
Keywords: Emotions